Faith in bikinis : politics and leisure in the coastal South since the Civil War - Stanonis, Anthony J. (Anthony Joseph) (Politics and culture in the twentieth-century South., 2014)
"This is a study of six beach resort communities on the U.S. South's Atlantic and Gulf coasts: Galveston, Biloxi, Panama City, St. Augustine, Myrtle Beach, and Virginia Beach. As these cities became leisure destinations in the late nineteenth and early twentieth centuries, Anthony Stanonis argues, they were forced to balance the competing demands of modernizing consumer culture and Southern traditionalism. They also participated in an especially delicate dance regarding race--one involving everything from cultural anxieties around tanning to a practical desire to tamp down the sort of racial conflict that might discourage tourism. Stanonis suggests that these negotiations were not always successful. Residents of the beach towns who did not profit from tourism and resented catering to outsiders' values, for example, sometimes struck back through acts of violence. Stanonis traces the rise of the infrastructure of tourism, the tensions of preserving the environment, and the development of a profitable industry in a clear and objective fashion. More importantly, he explores the complexities of race, ethnicity, sexuality, and the tensions between a resort's illegal underground and its 'family entertainment.' The text contains a breadth of archival sources--including the author's own personal collection. The sources blend the perspectives of boosters and developers with those of residents and tourists. Stanonis skillfully weaves the stories of actual people throughout the historical narrative he constructs, which makes the manuscript both more enjoyable and more relevant"--